Fossil rhinoceroses from the Limeworks cave, Makapansgat - Hooijer, D. A. (Bernard Price Institute for Palaeontological Research, 1959)
The rhinoceros remains from Makapansgat consist almost exclusively of milk molars. An investigation of the milk teeth of the two living African rhinoceroses Ceratotherium sinum and Diceros bicornis discloses adequate distinguishing characters on a basis of which both species are recognised to occur in the fossil collection. The white rhinoceros is the more abundant and the teeth appear rather larger than in the living races of C. sinum. The significance of the occurrence only of juvenile individuals is discussed.
Main article
Keywords: Rhinoceros; Makapansgat; molars